The Features and Characteristics of Composing the Monologue form of "Mohamed Abdel Wahab" Monologue (Malish amal) as a Model - jaradat, Rula (Dirasat: Human and Social Sciences, 2021)
Mohammed Abdul Wahab (1897-1991) is considered one of the most important pioneers of innovation in the art of singing, he wasn`t far from the artistic atmosphere full of social and artistic revolution, because of his contact with artists, especially in the theater, and his interest in European civilization.. The manifestations of renewal was clearly featured in the film song as it became light and short, and he added many musical instruments to the orchestra, also he used in some of his works western rhythms in addition to the Arabic rhythms. Abdul Wahab knocked all the Arabic singing forms, whether in what he sang himself or what he gave to singers, and some music came as a mixture between eastern and western, so the researcher saw the need to shed light on the features and characteristics of the monologue of Mohamed Abdel Wahab Monologue (Malish Amal feldunia), through specialized analytical study, which benefits those interested in this field and enriches the Arab Library with the works of one of the pioneers of composer. This research is divided into two parts: Part 1: Theoretical Framework - the template of the monologue in the 20th century. - Hussein Al Sayed Author (study sample). - Mohammed Abdul Wahab Composer (study sample). - Laila Murad Performer (study sample). Part 2: Practical Framework - General division and a detailed analytical study of the monologue (Malish Amal feldunia). - The results of the study, recommendations, and the list of references and then the summary of the study.